Sparks - Kennen, Ally (Marion Lloyd London, 2010)
When Carla's beloved grandfather dies, he leaves a letter for her telling her of his secret dream. Carla wants to make the dream come true, but is there any way a thirteen-year-old girl can give her grandfather a real Viking funeral? Suggested level: intermediate, junior secondary